Usaha Kerajinan Rambut sebagai Sentra Industri Kecil Penopang Kebutuhan Hidup Layak dan Alternatif Solusi Pengangguran di Desa Karangbanjar Kabupaten Purbalingga, 2011 - Rakhmat Priyono (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2012)
This research aims are to analyze the productivity, the labor absorption, and the living standard of labor in hair production centre in Karangbanjar village, Bojongsari district, Purbalingga regency. Hair production is the industry product which is one of advantage products in Purbalingga regency. This research is conducted with qualitative and quantitative analysis that uses output-input and regression to analyze the productivity, labor employed-labor force ratio to analyze the labor absorption, and total income-UMK and total income-KHL ratio to analyze living standard of labor. The results show that: (1) the productivity of labor is relatively high (Rp7.144.183,27/labor/month), and according to regression that material, capital, and wage cost affect production significantly; (2) the labor absorption of hair product enterprises is relatively high, shows 30,47 percents of population in Karangbanjar village; (3) According to UMK standard, the total income of 85 percents of them are more than living standard level, and according to KHL standard, it shows 82,5 percents. The income from these enterprises can rise up their living standard level until 10 percents significantly. Keywords: productivity, labor absorption, living standard, hair production